Indirect Spectrophotometric Determination of Cefalexin monohydrate, Ceftriaxone Sodium and Cefotaxim Sodium in Pharmaceuticals Using N-Bromosuccinimde and Evans Blue Dye - mohamed aghwan; Elham Al-Talibi (College of Education for Pure Sciences, 2020)
An indirect sensitive and selective spectrophotometric method has been developed for the determination of cephalexin monohydrate (CEM) ceftriaxone sodium (CFX) and cefotaxim sodium (CEF) in bulk and pharmaceutical formulation. The method is based on the oxidation of (CEM), (CFX) and (CEF) in hydrochloric acid medium with known excess on N-Bromosuccinimde and subsequent determination of unreacted oxidant by decolorization of Evans blue dye (EB) and measure the absorbance of residual dye at 608 nm. Calibration curves of evans blue dye in the presence of drugs were rectilinear over the ranges 1.0-9.0 , 1.0-8.0 and 1.0-9.0 µg/ml with molar absorptivity 2.75×104 , 9.28×104 and 7.81×104 l.mol-1.cm-1 and average recoveries 98.97, 102.08 and 100.08% for CEM, CFX and CEF respectively with RSD of less than 3.29%. The method was free from interference of many excipients and additives commonly found in pharmaceutical formulations. The developed method was successfully applied for determination of the studied drugs in their pharmaceutical formulation resulted in a good agreement with certified value and standard addition procedure.